2006
DOI: 10.1073/pnas.0602328103
|View full text |Cite
|
Sign up to set email alerts
|

Fragments of ATP synthase mediate plant perception of insect attack

Abstract: Plants can perceive a wide range of biotic attackers and respond with targeted induced defenses. Specificity in plant non-selfrecognition occurs either directly by perception of pest-derived elicitors or indirectly through resistance protein recognition of host targets that are inappropriately proteolyzed. Indirect plant perception can occur during interactions with pathogens, yet evidence for analogous events mediating the detection of insect herbivores remains elusive. Here we report indirect perception of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
265
1
4

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 360 publications
(288 citation statements)
references
References 39 publications
10
265
1
4
Order By: Relevance
“…A study on volicitin in the regurgitant of Spodoptera exigua showed that the initiation of the response of maize plants to feeding damage was mediated by a protein-ligand interaction in plasma membrane fractions (32). In cowpea, perception of Spodoptera frugiperda herbivory is mediated by fragments of ATP synthase that induce a targeted defense mechanism (27). Interestingly, herbivore saliva is not only able to elicit plant defense but is also able to suppress it (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study on volicitin in the regurgitant of Spodoptera exigua showed that the initiation of the response of maize plants to feeding damage was mediated by a protein-ligand interaction in plasma membrane fractions (32). In cowpea, perception of Spodoptera frugiperda herbivory is mediated by fragments of ATP synthase that induce a targeted defense mechanism (27). Interestingly, herbivore saliva is not only able to elicit plant defense but is also able to suppress it (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…The chemical nature of a few elicitors of feeding-induced plant defense responses are known: fatty acid-amino acid conjugates, including volicitin, of several lepidopterans (6,7,(23)(24)(25)(26); peptides derived by proteolysis from chloroplastic ATP synthase of herbivore-damaged plants (27,28); disulfo-oxy fatty acids of grasshopper regurgitant, named caeliferins (29); and the enzyme ␤-glucosidase from Pieris brassicae oral secretions (8). Application of these elicitors onto plant wounds results in the release of volatiles that repel ovipositing herbivores (30) or attract natural enemies of herbivores (31).…”
Section: Discussionmentioning
confidence: 99%
“…Plant endogenous peptide elicitors, systemin (Pearce et al, 1991), HypSys (Pearce et al, 2001a), AtPep (Huffaker et al, 2006), inceptin (Schmelz et al, 2006), GmSubPep (Pearce et al, 2010b), and Gmpep914/890 (this study), were initially purified biochemically using bioassays such as the induction of a defense response or medium alkalinization. These peptides are not similar at the amino acid sequence level, indicating that there will be difficulties elucidating novel endogenous peptide elicitors from databases.…”
Section: Discussionmentioning
confidence: 99%
“…When cowpea (Vigna unguiculata) leaves were consumed by Spodoptera frugiperda larvae and the oral secretions deposited on the leaves, a proteolyzed fragment of the cowpea chloroplastic ATP synthase produced in the insect gut was found to elicit defense responses (Schmelz et al, 2006). The peptide was termed inceptin and is an example of an indirect signal generated by the insect that initiates specific plant defense responses.…”
mentioning
confidence: 99%
“…Oligosaccharides induce production of defensive compounds under the infection of phytopathogens in the Castor bean, Ricinus commais (Bruce and West 1982). A peptide, inceptin, is one of the elicitors which induce volatile production in Cowpea plants (Schmelz et al 2006). The fraction larger than 3 kDa in molecular weight could contain oligosaccharides and polypeptides.…”
Section: Response Of a Ervi To Plants Treated With Artificial Diet Smentioning
confidence: 99%